Crossroads of the classroom : narrative intersections of teacher knowledge and subject matter - Ross, Vicki, 1958-; Chan, Elaine; Keyes, Dixie (Emerald Publishing, 2017)
This book aims to explore and make visible the intersection of subject matter knowledge and teacher knowledge in the narratives of teachers. This complicated interaction between these two bodies of knowledge is often studied and little understood.
Keywords: Education -- Research -- Methodology.; Narrative inquiry (Research method); Effective teaching.; Knowledge, Theory of.; elektronické knihy; electronic books